On Tang Junyi’s Critique of Anselm’s Argument for the Existence of God - Dai, Yumin (Religions, 2024)
Anselm’s argument for the existence of God posits that the concept of God inherently implies its existence. Tang Junyi critiques this argument from two fundamental angles. Firstly, he argues that the contingency of human thought places an unwarranted burden of proof on the existence of God, introducing an inherent contradiction within the argument’s premise. Secondly, he contends that Anselm’s argument fails to deduce the existence of God from empirical things. Tang’s empirical approach to critiquing the argument bears a superficial resemblance to St. Thomas Aquinas’s cosmological argument for God’s existence, yet a profound difference exists between the two, precluding their equivalence. Delving deeper, Tang’s critique is rooted in the Confucian philosophy. Nevertheless, Tang’s critique, while insightful, does not fully dismantle Anselm’s argument, underscoring the intrinsic differences and tensions between Chinese and Western perspectives on religion and philosophy.